Efektivitas Rejim Lingkungan Internasional: Analisis Komparatif terhadap Protokol Kyoto dan Kesepakatan Paris - Nugroho, Bambang Wahyu; Ghanem, Hamdi M.G.A.A (Frequency of International Relations (FETRIAN), 2025)
The persistent challenge of global environmental degradation underscores the critical need to evaluate the efficacy of international environmental regimes (IERs). This study conducts a rigorous comparative analysis of the Kyoto Protocol and Paris Agreement to identify determinants of regime effectiveness, conceptualized through compliance, empowerment, and socialization. Employing a mixed-methods approach—including qualitative document analysis, semi-structured interviews with key stakeholders, and quantitative assessment of emission data—we examine how regime design, contextual factors, and actor commitment influence outcomes. Our findings reveal that effectiveness is significantly constrained by structural asymmetries in commitments, inadequate verification mechanisms, and divergent national interests. While the Paris Agreement’s polycentric architecture offers greater adaptability, its reliance on voluntary Nationally Determined Contributions (NDCs) risks ambition gaps. The Kyoto Protocol’s binding targets suffered from limited participation and enforcement incapacity. We conclude that robust effectiveness requires adaptive frameworks integrating legally binding elements with equitable burden-sharing, stringent monitoring, reporting, and verification (MRV) systems, and enhanced legitimacy through inclusive governance. Policy implications emphasize redesigning compliance incentives and strengthening transnational accountability networks.